Deep Learning for Early Cancer Detection: A Comprehensive Analysis of Imaging Data - Gosavi, Chhaya; Naik, Anjali; Tasgaonkar, Madhuri (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This examination paper digs into the basic domain of early malignant growth location, zeroing in on cellular breakdown in the lungs, a noticeable reason for mortality. Current screening strategies frequently battle with precise division of assorted disease cell morphologies, prompting less than ideal dependability. Accordingly, we present a powerful screening method consolidating Otsu thresholding division, cuckoo search calculation enhancement, and nearby twofold examples including extraction. The following Convolutional Brain Organization (CNN) classifier actually recognizes threatening and non-harmful lung injuries, accomplishing an amazing 96.97% exactness. Our use of genetic algorithms and Particle Swarm Optimization to compile the results demonstrates a significant improvement in accuracy. This exploration contributes a promising system to the scene of early malignant growth identification, pushing for further developed screening accuracy and, thus, improved patient results.